Modelo de controle de acesso adaptativo - Cereda, Paulo Roberto Massa (2008)
Privacy has become an important aspect when modeling computational systems that have personal information and actions that deal with them. Control access models are used to provide security of such information. Some of these models, altough, are just applied to specific domains. It is proposed an access control model simple yet generic enough to comply with the security and privacy aspects of a system. The proposed model uses an adaptive automaton to perform the access control, and has a set of privacy commands, coded from a legislation or policy. These commands verify if a certain action in the systen may be characterized as a privacy violation. Moreover, the model may be used with auditing mechanisms to register actions in the system and guarantee the privacy.